PENGARUH MODEL ROLE PLAYING BERBANTUAN FLASHCARD TERHADAP PEMAHAMAN KONSEP PENDIDIKAN PANCASILA SISWA SEKOLAH DASAR - Intan Tri Wulandari intantriwulandari; Chairul Amriyah; Yudesta Ervayliana (Elementar : Jurnal Pendidikan Dasar, 2026)
Students' conceptual understanding in Pancasila Education at SD Negeri 2 Bandar Agung, North Lampung, remained relatively low due to teacher-centered instruction and the limited use of interactive learning media. This study introduces the integration of the Role Playing learning model assisted by Flashcard media to improve elementary school students' conceptual understanding, addressing the limited previous studies that have combined both approaches in Pancasila Education. This study aimed to determine the effect of the Role Playing learning model assisted by Flashcards on students' conceptual understanding. A quantitative approach with a quasi-experimental design using a non-equivalent control group design was employed. The participants consisted of 30 fourth-grade students, divided equally into an experimental class (n = 15) and a control class (n = 15). Data were collected using a conceptual understanding test that had been validated and tested for reliability. Data were analyzed using an Independent Sample t-test at a significance level of 0.05. The results revealed a significant difference between the two groups (t = -3.157, df = 28, p = 0.004). Furthermore, the calculated effect size (Cohen's d = 1.15) indicated a large practical effect, showing that students taught using the Role Playing learning model assisted by Flashcards achieved higher conceptual understanding than those taught using the Discovery Learning model. Therefore, the implementation of the Role Playing learning model assisted by Flashcards is effective in improving elementary school students' conceptual understanding in Pancasila Education. Keywords: Role Playing, Cooperative Learning, Conceptual Understanding.